PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH ORGANIK RUMAH TANGGA DI DESA PENIMBUNG KECAMATAN GUNUNGSARI KABUPATEN LOMBOK BARAT - Pramuda, Lalu Cipta Galuh; Paryantini, Izma; Maulida, Namira Putri; Khawarizmi, Bunial; Rahmi, Sri Helmayana; Almujaddidy, Ulul Albab; Saren, Anggya Nurakhmadya; Swari, Vista Citra Puspita; Oktafianingsih, Erni; Marjan, Luluk Fahrani Wal; Putra, Ida Bagus Giri (Universitas Mataram, 2023)
Penimbung Village is one of the villages in the Gunungsari District, West Lombok Regency. Penimbung Village has an area of 420 hectares or 4.2 acres, which consists of 7 main hamlets and 3 preparatory hamlets. The waste problem in Penimbung Village is a serious problem because there is no Final Garbage Disposal Site (TPS). The lack of public knowledge regarding the use of organic waste is also a major problem. The purpose of this activity is to increase public knowledge regarding the use of organic waste to become liquid organic fertilizer so that it has use value for the environment. The method used in this activity is counseling and demonstration. The community paid attention to the material presented and then continued with a demonstration of making and assisting in the manufacture of liquid organic fertilizer. From the evaluation results, it was found that the community felt helped by this activity and gained knowledge about how to process household waste, especially organic waste. Community empowerment activities in Penimbung Village through training in the manufacture of liquid organic fertilizer have again introduced the community to the concept of advanced and sustainable agriculture where the utilization of waste, apart from providing use value for the environment, can also reduce expenditure on purchasing fertilizers for agriculture.